Identification of Key Pathways Involved in White Strain of Hypsizygus marmoreus Extracts-Induced Cell Death of Human Hepatoma Hep3B Cells by Next Generation Sequencing - Li, Wei-Sung; Lee, Kun-Tsung Denzel; Chen, Li-Yun; You, Bang-Jau; Lee, Hong-Zin (Frontiers in Pharmacology, 2022)
White strain of Hypsizygus marmoreus is named as white genius mushroom (WGM) and is a popular food in Taiwan. We have confirmed the cytotoxicity of WGM extracts on human Hep3B liver cancer cells. A total of 8711 significantly differential genes were identified through large-scale transcriptome sequencing. According to the KEGG pathway enrichment analysis, autophagy, mitophagy and apoptosis pathways were identified as significant in WGM extracts-treated cells. WGM extracts induced a dose-dependent generation of reactive oxygen species (ROS) and membrane-enclosed vacuoles in Hep3B cells. The inhibition of ROS by the ROS scavengers blocked the induction of cell death and vacuoles formation. We suggested that the cell death and membrane-enclosed vacuoles induced by WGM extracts are dependent on ROS production in Hep3B cells. (2E,6E)-3,7,11,15,19,23,27,31,35-Nonamethylhexatriaconta-2,6,34-triene-1,11,15,19,23,27,31-heptol and (18:2) lysophosphatidylcholine were identified in WGM extracts. In addition to being a very popular edible mushrooms, WGM may be developed into a dietary supplement or dietary chemopreventive agent for the cancer treatment.